2011
DOI: 10.1007/s12672-011-0069-3
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Receptor Profiling of Ovarian Granulosa Cell Tumors

Abstract: Granulosa cell tumors of the ovary (GCT) represent ~5% of malignant ovarian tumors. The adult form is defined by a mutation in the FOXL2 gene. GCT exhibit many of the features of normal proliferating granulosa cells. We have profiled the expression of the 48 human nuclear receptors (NR) by quantitative RT-PCR in a panel of GCT and in two GCT-derived cell lines, COV434 and KGN. The highest level of expression is seen for COUP-TF2 with abundant expression of PPARγ, SF-1, and TR-α. Estrogen receptor (ER)-β is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 104 publications
4
38
0
Order By: Relevance
“…The percentage of mutated tumors in the reviewed series was consistent with existing reports, ranging from 70.4% to 100% (mean, 91.9%). The FOXL2 mutation occurred in more than 90% of mutated tumors in all but two studies (Alexiadis et al 2011;D'Angelo et al 2011), in which FOXL2 mutation occurred in 70.4% and 85.7% of tumors. Excluding this study, the FOXL2 mutation occurred in 94.0% of AGCTs.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The percentage of mutated tumors in the reviewed series was consistent with existing reports, ranging from 70.4% to 100% (mean, 91.9%). The FOXL2 mutation occurred in more than 90% of mutated tumors in all but two studies (Alexiadis et al 2011;D'Angelo et al 2011), in which FOXL2 mutation occurred in 70.4% and 85.7% of tumors. Excluding this study, the FOXL2 mutation occurred in 94.0% of AGCTs.…”
Section: Discussionmentioning
confidence: 93%
“…In humans, FOXL2 is expressed almost exclusively in ovarian tissue, in which it is involved in ovarian development (Cocquet et al 2002;Schmidt et al 2004). It has been reported that the somatic mutation in FOXL2 gene (c.402C>G) is present in more than 95% of ovarian AGCTs, but not in several other neoplasms (Schrader et al 2009;Shah et al 2009;Benayoun et al 2010;Jamieson et al 2010;Kim et al 2010a;Lee et al 2010;Al-Agha et al 2011;Alexiadis et al 2011;D'Angelo et al 2011;Gershon et al 2011;Hes et al 2011). Although the functional consequence of the missense mutation remain unclear, Benayoun et al (2013) reported that FOXL2 mutation induced genes that are associated with faster cell cycling and the downregulation of genes associated with cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hormonal therapy: Hormone treatment is a logical treatment for advanced GrCT, given their frequent oestrogen dependence and usually indolent course (51). Bone density monitoring is indicated for patients receiving aromatase inhibitors, as is the standard of care in breast cancer treatment.…”
Section: Treatment Surgerymentioning
confidence: 99%
“…Because the expression pattern of NR genes in different tissues may suggest their relative functional importance in different tissues, expression profiling of NRs has greatly facilitated our understanding of the physiological functions of these receptors (12)(13)(14)(15)(16)(17)(18). The expression of the entire NR transcriptome was characterized by Mangelsdorf and colleagues; in their work, all 49 mouse NR mRNAs were measured via quantitative RT-PCR (QPCR) in 39 tissues (17).…”
mentioning
confidence: 99%